Boosting Punctuation Proficiency: The Power of an Interactive Chatbot for EFL Learners - Ali Al Ghaithi; Behnam Behforouz (Journal of Language and Education)
Background: While technology is becoming more integrated into education, little research has been done on the contribution that chatbots must play when it comes to helping EFL learners gain some language ability, like grammar. Most current research focuses on vocabulary or learning grammar and thus does not understand how interactive, computer-based technologies can help develop rule-based writing skills. This study fills this gap by identifying the degree to which a WhatsApp chatbot improves punctuation skills, thus gaining insight into the promise of chatbot-enhanced teaching for certain language subskills.